2018
DOI: 10.3390/jof4040123
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans as a Model Host to Monitor the Candida Infection Processes

Abstract: C. elegans has several advantages as an experimental host for the study of infectious diseases. Worms are easily maintained and propagated on bacterial lawns. The worms can be frozen for long term storage and still maintain viability years later. Their short generation time and large brood size of thousands of worms grown on a single petri dish, makes it relatively easy to maintain at a low cost. The typical wild type adult worm grows to approximately 1.5 mm in length and are transparent, allowing for the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 140 publications
(183 reference statements)
0
27
0
Order By: Relevance
“…Therefore, studies of screening for identifying virulence factors of pathogenic microorganisms using mammals are not easy, because many animals are required. To overcome these problems, infection models using invertebrates such as fruit flies, nematodes, and greater wax moths have been proposed . Invertebrate animals generally have the following benefits compared with mammals: (i) lower cost of breeding the animals, (ii) larger numbers of individuals can be reared in a small space, (iii) fewer ethical problems concerning killing the animals, and (iv) fewer samples needed because of the smaller body sizes (Table ) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies of screening for identifying virulence factors of pathogenic microorganisms using mammals are not easy, because many animals are required. To overcome these problems, infection models using invertebrates such as fruit flies, nematodes, and greater wax moths have been proposed . Invertebrate animals generally have the following benefits compared with mammals: (i) lower cost of breeding the animals, (ii) larger numbers of individuals can be reared in a small space, (iii) fewer ethical problems concerning killing the animals, and (iv) fewer samples needed because of the smaller body sizes (Table ) .…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to use invertebrates such as nematodes (Caenorhabditis elegans), fruit flies (Drosophila melanogaster), greater wax moths (Galleria mellonella), and silkworms (Bombyx mori) as models for drug discovery research. [6][7][8][9][11][12][13][14] Nematodes and fruit flies have advantages in genetic research, but because of their small size it is difficult to perform quantitative administration of sample solutions into their blood and perform biochemical experiments that require insect blood samples (Table 1). Therefore, there has been little research on the screening and optimization of compounds based on the evaluation of therapeutic effects by injection.…”
Section: Benefits Of Using Insects In Basic Stud-ies For Drug Discoverymentioning
confidence: 99%
“…Many infectious disease models using insects such as nematodes, fruit flies, greater wax moths, and silkworms have been established. 9,13,14,17,[25][26][27][28][29][30][31][32][33][34][35][36] These infection models are based on the death of insects with the administration of pathogenic microorganisms. Large-scale in vivo screening has identified virulence genes of pathogens and defense-related genes of hosts.…”
Section: Human Disease Models Using Insectsmentioning
confidence: 99%
“…We found that beneficial yeasts were able to inhibit adhesion and germ tube development when applied 2 hours after C. albicans had attached to the abiotic surfaces ( Beneficial yeasts protect nematodes from C. albicans infections C. elegans is an ideal experimental host system to study microbial interactions in the gastrointestinal tract. The nematode gut faithfully recapitulates a mammalian intestine in anatomy, innate immunity, and neuronal circuits (Elkabti et al, 2018, Schulenburg et al, 2004. Microbes introduced via the diet are established as the gut microbiome of the nematode thereby allowing the investigator to manipulate the intestinal microbiome.…”
Section: Beneficial Yeasts Prevent Attachment and Invasion Of C Albimentioning
confidence: 99%